(untitled) (Physical Education, Health and Social Sciences, 2025)
This study is focused to investigate macronutrients and in-vivo anti-inflammatory activity of Tamaricaria elegans Royle (Tamaricaceae) using rat paw edema model. Shade dried plant was exhaustively extracted by maceration with methanol (80%) to get crude methanol extract (a), followed by fractionation with different organic solvents to get pet-ether (b), chloroform (c), ethyl acetate (d) and butanol (e) fractions. Fraction (c) was found to be the most potent inhibitor of carragenin induced edema with 67.65% inhibition during 1 h at a dose of 100 mg/kg followed by 66.67% and 62.50% at 3 and 5 h, respectively. Like aspirin -a COX inhibitor, the plant has also demonstrated sustained inhibition of edema both at early and later phase of the experiment. Such aspirin like sustained effect is more likely due to COX inhibition, which may be attributed to triterpenes content of the plant.